2006
DOI: 10.1097/01.ogx.0000206353.22975.c5
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Cisplatin and Paclitaxel in Ovarian Cancer

Abstract: This study was conducted to identify the method of laparoscopic entry used by practicing gynecologists and learn whether they are following new recommendations for improvement of the safety of laparoscopic gynecologic surgery. Several international societies of endoscopy have endorsed new guidelines for safe laparoscopic entry techniques. Physicians are advised to place the primary incision in the base of the umbilicus when performing closed laparoscopy. If adhesions are suspected, the incision can be made in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
417
0
19

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(443 citation statements)
references
References 0 publications
7
417
0
19
Order By: Relevance
“…Grade ¾ toxicity was significantly greater and quality of life scores significantly worse in the IP arm. [26] Elit et al published a meta-analysis of 7 randomized controlled trials for adjuvant intraperitoneal chemotherapy. A pooled analysis from 6 of the 7 studies confirmed the survival benefit of IP chemotherapy compared with IV chemotherapy alone (Relative risk, 0.88; 95 % confidence interval, 0.81-0.95) Adverse events and catheter related problems were more common in the IP chemotherapy group and often led to discontinuation of therapy.…”
Section: Rational For Intraperitoneal Chemotherapy For Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Grade ¾ toxicity was significantly greater and quality of life scores significantly worse in the IP arm. [26] Elit et al published a meta-analysis of 7 randomized controlled trials for adjuvant intraperitoneal chemotherapy. A pooled analysis from 6 of the 7 studies confirmed the survival benefit of IP chemotherapy compared with IV chemotherapy alone (Relative risk, 0.88; 95 % confidence interval, 0.81-0.95) Adverse events and catheter related problems were more common in the IP chemotherapy group and often led to discontinuation of therapy.…”
Section: Rational For Intraperitoneal Chemotherapy For Ovarian Cancermentioning
confidence: 99%
“…[13,14,25,26,[51][52][53][54][55][56][57]. Thus, most of the results obtained with the addition of HIPEC to standard frontline therapy seem to be similar or inferior to the results obtained without the use of HIPEC.…”
Section: Hipec As First Line Therapy For Ovarian Cancermentioning
confidence: 99%
“…The median progression-free survival and overall survival from landmark phase III trials range between 12 and 24 months and 29-65 months, respectively. 1,2 Factors that are believed to impact survival include patient age, performance status, preoperative CA125, volume of ascites, stage, grade, extent of cytoreductive surgery, chemotherapeutic agents, route of delivery, duration of treatment, histological subtype, host immune response, and specific genetic alterations, including BRCA mutations. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] There remains, however, limited ability to accurately prognosticate in patients with advanced stage high-grade serous carcinoma based on features of the primary tumor at the time of diagnosis.…”
mentioning
confidence: 99%
“…Since the introduction of platinum compounds in first-line chemotherapy, PFS has not improved much over the years, but OS has risen from about 20 months in the 1980s (Conte et al, 1986;Alberts et al, 1992;Rothenberg et al, 1992;Swenerton et al, 1992;Alberts et al, 1996) to 30 months in the 1990s (McGuire et al, 1996;ICON Collaborators, 1998;Muggia et al, 2000) and 40 months in the last few years (Markman et al, 2001;ICON Collaborators, 2002;Du Bois et al, 2003;Armstrong et al, 2006). In our series, PFS was slightly better than is commonly reported and considering the composition of our population, OS of 54 months is remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, PFS was slightly better than is commonly reported and considering the composition of our population, OS of 54 months is remarkable. Comparable results are reported only in trials that enrolled only patients with minimal or no residual disease after the first surgery (Alberts et al, 1996;Markman et al, 2001;ICON Collaborators, 2002;Armstrong et al, 2006), and in other studies that considered the subgroup of patients with this positive prognostic factor (du Bois et al, 2006;Pfisterer et al, 2006).…”
Section: Discussionmentioning
confidence: 99%